Manipulating all-pH hydrogen evolution kinetics on metal sulfides through one-pot simultaneously derived multi-interface engineering and phosphorus doping. Issue 45 (10th November 2021) - Wang, Haiqing; Ma, Mingjun; Li, Junjun; Zhang, Zhicheng; Zhou, Weijia; Liu, Hong
Abstract : The all-pH hydrogen evolution kinetics on metal sulfides was greatly promoted through one-pot simultaneously derived multi-interface engineering and phosphorus doping. Abstract : The hydrogen evolution reaction (HER) especially at all pH is very significant for the electrocatalytic production of hydrogen energy, which consists of three key processes, i.e., water dissociation, hydroxide desorption and hydrogen combination. Herein, we developed a one-pot simultaneously derived multi-interface engineering and phosphorus doping strategy to promote all-pH hydrogen evolution kinetics on metal sulfides through constructing hierarchical NiS/WS2 /Ni3 S4 hybrid frameworks. NiS/WS2 /Ni3 S4 is composed of strongly cross-linked WS2 nanosheets and NiS/Ni3 S4 nanoparticles featuring highly exposed heterogeneous interfaces and phosphorus doping. NiS/WS2 /Ni3 S4 only requires overpotentials of about 50 mV and 61 mV to drive 10 mA cm −2 in alkaline and acid media, respectively, thereby being classified into one of the best transition metal sulfide (TMS) electrocatalysts. The robust all-pH HER activity of NiS/WS2 /Ni3 S should originate from the rapid transfer/transport of electrons and mass triggered by the special hierarchical structures and the multi-interface electron effects induced by the collaboration of interfaces and phosphorus doping with different capabilities for the adsorption and desorption of H*, H2 O* and H⋯OH*.